Treatment intensification with maraviroc (CCR5 antagonist) leads to declines in CD16-expressing monocytes in cART-suppressed chronic HIV-infected subjects and is associated with improvements in neurocognitive test performance: implications for HIV-associated neurocognitive disease (HAND) - Ndhlovu, Lishomwa C.; Umaki, Tracie; Chew, Glen M.; Chow, Dominic C.; Agsalda, Melissa; Kallianpur, Kalpana J.; Paul, Robert; Zhang, Guangxiang; Ho, Erika; Hanks, Nancy; Nakamoto, Beau; Shiramizu, Bruce T.; et al. (Journal of neurovirology, 2014)
HIV-associated neurocognitive disorders (HAND) continues to be prevalent (30–50 %) despite plasma HIV-RNA suppression with combination antiretroviral therapy (cART). There is no proven therapy for individuals on suppressive cART with HAND. We have shown that the degree of HIV reservoir burden (HIV DNA) in monocytes appear to be linked to cognitive outcomes. HIV infection of monocytes may therefore be critical in the pathogenesis of HAND. A single arm, open-labeled trial was conducted to examine the effect of maraviroc (MVC) intensification on monocyte inflammation and neuropsychological (NP) performance in 15 HIV subjects on stable 6-month cART with undetectable plasma HIV RNA (<48 copies/ml) and detectable monocyte HIV DNA (>10 copies/10 6 cells). MVC was added to their existing cART regimen for 24 weeks. Post-intensification change in monocytes was assessed using multiparametric flow cytometry, monocyte HIV DNA content by PCR, soluble CD163 (sCD163) by an ELISA, and NP performance over 24 weeks. In 12 evaluable subjects, MVC intensification resulted in a decreased proportion of circulating intermediate (median; 3.06 % (1.93, 6.45) to 1.05 % (0.77, 2.26)) and nonclassical (5.2 % (3.8, 7.9) to 3.2 % (1.8, 4.8)) CD16-expressing monocytes, a reduction in monocyte HIV DNA content to zero log 10 copies/10 6 cells and in levels of sCD163 of 43 % by 24 weeks. This was associated with significant improvement in NP performance among six subjects who entered the study with evidence of mild to moderate cognitive impairment. The results of this study suggest that antiretroviral therapy with potency against monocytes may have efficacy against HAND.